The romantic heroine: "I am not more beautiful when I keep quiet and when I am submissive" - Achón Lezaun, Irene (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
In this article we are going to analyze a figure and a period that have taught us the weight of society that women, since our childhood, have suffered. The romantic heroine and the legacy that Romanticism left us are going to help us to understand that the fight started many centuries ago: they tried we kept quiet and were submissive, but they have not yet done so.